2015
DOI: 10.1136/bmjopen-2015-007698
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a pre-implementation and post-implementation study on shared decision-making in the surgical treatment of women with early-stage breast cancer

Abstract: BackgroundThe majority of patients diagnosed with early-stage breast cancer are in a position to choose between having a mastectomy or lumpectomy with radiation therapy (breast-conserving therapy). Since the long-term survival rates for mastectomy and for lumpectomy with radiation therapy are comparable, patients’ informed preferences are important for decision-making. Although most clinicians believe that they do include patients in the decision-making process, the information that women with breast cancer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…These strategies must also consider the individual providers and their beliefs and biases. Efforts to reduce provider bias could potentially include improved patient or physician education (49) and implementation of shared decision-making tools (50,51). Reimbursement reform represents a clear but complex measure that has the capacity to influence patterns of care.…”
Section: Discussionmentioning
confidence: 99%
“…These strategies must also consider the individual providers and their beliefs and biases. Efforts to reduce provider bias could potentially include improved patient or physician education (49) and implementation of shared decision-making tools (50,51). Reimbursement reform represents a clear but complex measure that has the capacity to influence patterns of care.…”
Section: Discussionmentioning
confidence: 99%
“…This includes patients and physicians having a shared understanding of the problem, patients being fully informed of treatment options and the risks and benefits, and patients and physicians making treatment decisions based on clinical evidence and patients’ values and preferences [10,11]. Patients who engage in shared decision-making with their physicians report better understanding of treatment options [1116], higher confidence in decisions made [15,16], higher treatment compliance [16], greater satisfaction with care/decision [16], and better quality of life [17]. Alternatively, the lack of patient involvement in treatment decision-making has been linked with anxiety, dissatisfaction with care, and decision regret [1820].…”
Section: Introductionmentioning
confidence: 99%
“…These groups experience greater challenges, as cultural as well as linguistic factors may affect their interactions with the medical environment [21]. There is increasing evidence that many patients want to be involved in treatment decisions [15,25]; however, non-cancer studies indicate that racial/ethnic minorities report less involvement in treatment decision-making [26]. In this study, we expand our understanding of shared decision-making in a multiethnic and multilingual population of prostate cancer survivors by exploring racial and ethnic differences in (1) their perception of their doctors requesting their engagement in decision-making, and (2) their self-reported involvement in treatment decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…31 Efforts to reduce provider bias could potentially include the increased use of multidisciplinary clinics, improved patient or physician education, 22 or implementation of shared decision making tools. 32 Shared decision aids have been shown to increase patient knowledge about surgical treatment options in early-stage breast cancer 33 and when used in a randomized trial setting, have been shown to increase the rate of breast conservation from 76% to 94%. 34 Multi-disciplinary tumor board conferences have been reported to Median Odds Ratio of provider increase recommendations for breast conservation.…”
Section: Discussionmentioning
confidence: 99%